2016
DOI: 10.1542/peds.2015-4268c
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities During Early Life for Cancer Prevention: Highlights From a Series of Virtual Meetings With Experts

Abstract: Compelling evidence suggests that early life exposures can affect lifetime cancer risk. In 2014, the Centers for Disease Control and Prevention’s (CDC’s) Cancer Prevention Across the Lifespan Workgroup hosted a series of virtual meetings with select experts to discuss the state of the evidence linking factors during the prenatal period and early childhood to subsequent risk of both pediatric and adult cancers. In this article, we present the results from a qualitative analysis of the meeting transcripts and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Recently, our research group has suggested that the time is right to develop activities focused on primary prevention of childhood leukemia. 185,186 …”
Section: A Clinical Perspective On Environmental Health Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our research group has suggested that the time is right to develop activities focused on primary prevention of childhood leukemia. 185,186 …”
Section: A Clinical Perspective On Environmental Health Literacymentioning
confidence: 99%
“…While the CDC has been exploring opportunities for early life prevention of child and adult cancers, there are diverse opinions about whether there is an adequate evidence base for primary prevention of cancer. 185 In a summary of expert opinion on what evidence should be necessary to support taking action, suggestions range from animal studies and toxicologic profiles to high quality systematic reviews (see Text Box 2). 185 …”
Section: A Clinical Perspective On Environmental Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of webinars held over 1 year, we engaged experts in discussions to help clarify our understanding of the scientific literature and its application for public health. The article by Holman et al 10 summarizes the themes that emerged from those discussions. Other articles in this special supplement were contributed by participants in the webinars, and they expand on specific topics.…”
mentioning
confidence: 99%
“…In this article, we highlight factors that were selected on the basis of several criteria. The factors we examined (1) occurred in early life (in the prenatal period through age 10); (2) were identified by a group of subject matter experts consulting with the Centers for Disease Control and Prevention (CDC) 2 ; and (3) had at least 1 meta-analysis that demonstrated an empirical association with cancer occurrence. Based on these criteria, we selected the following factors: adverse childhood experiences 3 ; maternal alcohol consumption in pregnancy 4 ; assisted reproductive technology (ART) 5, 6 ; childhood obesity 7, 8 ; high or low birth weight 911 ; exposure to radiation, 12, 13 benzene, 14, 15 pesticides, or insecticides 1619 ; isolated cryptorchidism 10, 20 ; early onset of puberty 2123 ; exposure to parental tobacco smoke in utero 24, 25 and in childhood 26 ; allergies, asthma, and atopy 2729 ; and early exposure to infection and early day care.…”
mentioning
confidence: 99%